ANALISIS TINGKAT RISIKO CEDERA OVERUSE BERDASARKAN FAKTOR LATIHAN PADA PEMAIN SEKOLAH SEPAK BOLA AD’SPORT SOCCER SCHOOL - Kiki Wulandari; Joan Siswoyo; Muhammad Fajril Rifaldo; Candra Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the level of overuse injury risk and to analyze train-ing factors related to the level of overuse injury risk. The population in this study consists of Ad’Sport Soccer School players aged 13-17 years, totaling 30 players, with a total sampling method where the entire population is used as the sample. The research method used is quantitative descriptive. The instrument employed to collect data is a closed questionnaire, with data analysis using descriptive statis-tical percentages. The results of the study indicate that the level of overuse injury risk based on training factors, as assessed from all indicators, falls into the very high category, with a percentage of 33%, corresponding to 10 players. The risk of overuse injury, assessed from the warm-up and cool-down indicators, falls into the very high category at 30%, corresponding to 9 players. The risk of overuse injury, evaluated from the training frequency indicator, is categorized as low at 40%, corresponding to 12 players. The risk of overuse injury, based on the train-ing duration indicator, is categorized as moderate at 40%, corresponding to 12 players. The training intensity indicator is categorized as moderate at 43%, cor-responding to 13 players. The rest and recovery indicator is categorized as low at 30%, corresponding to 9 players. Overall, the risk of overuse injury is catego-rized as moderate at 37%, corresponding to 11 players.